Effect of Fermented Water Hyacinth (Eichhornia crassipes) Meal Using A Cow Rumen Fluid in Diets on Growth of River Carp (Leptobarbus hoevenii) Fingerling - Ferdhi Aulio Rahmad; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted for 56 days from June to August 2016. The aim of this research was to know of river carp (Leptobarbus hoevenii) fingerling on water hyacinth fermentations. This study uses a completely randomized design (CRD) with one factor, five level treatments and three replications. The fish used in this research with size 5-7 cm in 7,2 – 8,6 g in weight. Fish were reared in 1 m3 in cages with stocking density of 20/cage. feeding trials were replacing with soybean meal with water hyacinth fermentation applied to 0, 30, 40, 50 and 60% for 30% protein content. Result showed that fermentation of water hyacinth have significant effect (P<0,05) on growth, feed efficiency, and protein retentions. Replacement 30% of water hyacinth fermentation is the best resposn, produce the highest growth 0,56%, feed efficiency 13,9%, protein retention 17,80% and feed digestion respectively 52,83%.Key word : Leptobarbus hoevenii, Water Hyacinth, Fermentation, Rumen Fluid